2004
DOI: 10.1073/pnas.0308681101
|View full text |Cite
|
Sign up to set email alerts
|

Transgene-driven expression of the Doppel protein in Purkinje cells causes Purkinje cell degeneration and motor impairment

Abstract: The Doppel (Dpl) and Prion (PrP) proteins show 25% sequence identity and share several structural features with only minor differences. Dpl shows a PrP-like fold of its C-terminal globular domain and lacks the flexible N-terminal tail. The physiological functions of both proteins are unknown. However, ubiquitous Dpl overexpression in the brain of PrP knockout mice correlated with ataxia and Purkinje cell degeneration in the cerebellum. Interestingly, a similar phenotype was reported in transgenic mice expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 49 publications
0
41
0
Order By: Relevance
“…However, others, such as Zrch I and Npu, neither ectopically expressed Dpl nor exhibited ataxia and Purkinje cell degeneration (4,5). It was finally confirmed that Dpl is neurotoxic, and PrP C antagonizes the neurotoxicity of Dpl by a demonstration that transgenically expressed Dpl caused ataxia and Purkinje cell degeneration in nonataxic Zrch I Prnp 0/0 mice but not in wild-type mice (7)(8)(9). However, the exact mechanism of the antagonistic interaction of PrP C and Dpl remains unknown.…”
Section: The Normal Prion Protein (Prpmentioning
confidence: 70%
See 2 more Smart Citations
“…However, others, such as Zrch I and Npu, neither ectopically expressed Dpl nor exhibited ataxia and Purkinje cell degeneration (4,5). It was finally confirmed that Dpl is neurotoxic, and PrP C antagonizes the neurotoxicity of Dpl by a demonstration that transgenically expressed Dpl caused ataxia and Purkinje cell degeneration in nonataxic Zrch I Prnp 0/0 mice but not in wild-type mice (7)(8)(9). However, the exact mechanism of the antagonistic interaction of PrP C and Dpl remains unknown.…”
Section: The Normal Prion Protein (Prpmentioning
confidence: 70%
“…In contrast, Dpl, the first identified structural homologue of the C-terminal domain of PrP C , is neurotoxic causing ataxia and Purkinje cell degeneration in mice (7)(8)(9). Interestingly, PrP C functionally antagonizes the neurotoxicity of Dpl, preventing the neurode- generation (7)(8)(9). However, the mechanism of the antagonistic interaction between PrP C and Dpl or the truncated PrPs remains to be elucidated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…PrP C Expression Blocks Dpl-induced Toxicity-A key criterion to assess the accuracy of the in vitro model described above is the protective effect of PrP C expression, as this has been documented in all transgenic paradigms examined to date (20,22,41,42). Because cerebellar cells overexpressing hamster PrP C derived from Tg(SHaPrP)7 mice (35) were resistant to the toxic effect of Dpl (not shown), as in Tg mice (20,43), we investigated whether this was also the case for PrP C expressed at endogenous levels.…”
Section: Resultsmentioning
confidence: 99%
“…PCs present no signs of degeneration because of enhancer-mediated splicing that prevents F35 expression in these neurons (Shmerling et al, 1998). However, targeted-PC expression of the F35 construct by a specific promoter induces PC death and ataxia (Anderson et al, 2004;Flechsig et al, 2003). Similarly to Dpl-mediated degeneration, Shmerling syndrome is rescued by reintroducing the full-length Prnp (Shmerling et al, 1998).…”
Section: Other Prp C Mutant Mice: the Puzzle Of Functions Increasesmentioning
confidence: 99%